Social and Self-Reflective Use of a Web-Based Personally Controlled Health Management System - Lau, Annie YS; Dunn, Adam G; Mortimer, Nathan; Gallagher, Aideen; Proudfoot, Judith; Andrews, Annie; Liaw, Siaw-Teng; Crimmins, Jacinta; Arguel, Amaël; Coiera, Enrico (JMIR Publications, 2013)
BackgroundPersonally controlled health management systems (PCHMSs) contain a bundle of features to help patients and consumers manage their health. However, it is unclear how consumers actually use a PCHMS in their everyday settings. ObjectiveTo conduct an empirical analysis of how consumers used the social (forum and poll) and self-reflective (diary and personal health record [PHR]) features of a Web-based PCHMS designed to support their physical and emotional well-being. MethodsA single-group pre/post-test online prospective study was conducted to measure use of a Web-based PCHMS for physical and emotional well-being needs during a university academic semester. The PCHMS integrated an untethered PHR with social forums, polls, a diary, and online messaging links with a health service provider. Well-being journeys additionally provided information to encourage engagement with clinicians and health services. A total of 1985 students and staff aged 18 and above with access to the Internet were recruited online, of which 709 were eligible for analysis. Participants' self-reported well-being, health status, health service utilization, and help-seeking behaviors were compared using chi-square, McNemar's test, and Student's t test. Social networks were constructed to examine the online forum communication patterns among consumers and clinicians. ResultsThe two PCHMS features that were used most frequently and considered most useful and engaging were the social features (ie, the poll and forum). More than 30% (213/709) of participants who sought well-being assistance during the study indicated that other people had influenced their decision to seek help (54.4%, 386/709 sought assistance for physical well-being; 31.7%, 225/709 for emotional well-being). Although the prevalence of using a self-reflective feature (diary or PHR) was not as high (diary: 8.6%, 61/709; PHR: 15.0%, 106/709), the proportion of participants who visited a health care professional during the study was more than 20% greater in the group that did use a self-reflective feature (diary: P=.03; PHR: P<.001). ConclusionsThere was variation in the degree to which consumers used social and self-reflective PCHMS features but both were significantly associated with increased help-seeking behaviors and health service utilization. A PCHMS should combine both self-reflective as well as socially driven components to most effectively influence consumers' help-seeking behaviors.